2022
DOI: 10.1186/s40066-022-00381-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of large-scale agricultural investments on the food security status of local community in Gambella region, Ethiopia

Abstract: Background The government of Ethiopia has been promoting large-scale agricultural investments to accelerate agricultural modernization and improve local people’s food security. However, studies that quantify the actual impact of such investments on the food security status of the investment hosting community using diverse food security indicators and suitable impact estimation methods are scanty. The main purpose of this article is, therefore, to analyse the impact of large-scale agricultural i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
2
4
0
Order By: Relevance
“…These investments have decreased the local population's access to, utilisation of, and availability of food and have raised their susceptibility to food insecurity. These findings align with the results of [ 20 , 21 , 71 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These investments have decreased the local population's access to, utilisation of, and availability of food and have raised their susceptibility to food insecurity. These findings align with the results of [ 20 , 21 , 71 ].…”
Section: Resultssupporting
confidence: 92%
“…The results revealed that the households residing in communities without land investments are more likely to be food secure by 0.2% than households in communities with. These findings concur with those of Guyalo et al [ 20 ] that found that land investments negatively impact the livelihoods and food security of the households in the communities that they exist; but contrary to that of Fitawek and Hendrick [ 29 ] who found a positive relationship between land investments and household food security. The reason for the adverse effect could be attributed to the following reasons.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…However, the fundamental issue in this model is that we cannot estimate. ∂i = Y 1i − Y 0i for each household i, for the reason that two potential outcomes (Y 1 − Y 0 ) for the same household cannot be observed simultaneously (Guyalo et al, 2022). The unobserved outcome is often called the counterfactual outcome (Rosenbaum and Rubin, 1983) -"What would have happened to the wages and labour hours of the households who are exposed to the investments if they had not been exposed to or experienced such event".…”
Section: The Empirical Modelmentioning
confidence: 99%